Clinical partners' reflections on Indigenous curricula in health education and the development of a pre-clinical placement student toolkit. Issue 2 (4th March 2021) - Lucas, Cherie; Aly, Mariyam; Power, Tamara
ABSTRACT: Indigenous healthcare models are intergenerational, holistic, culturally appropriate and tailored to the needs of individual communities. To ensure that students working in Indigenous communities can engage appropriately and respectfully, they may require additional support for that learning. This study explores the recommendations of Clinical Partners based on their reflections and experiences working with Indigenous communities to outline inclusions and resources for Indigenous curricula, and the development of a toolkit designed to support students on clinical placement. A 45-min focus group or online survey (for remote participants) was conducted with clinical partners (n = 14) across seven health disciplines. Data were analysed thematically. Academic clinical partners reflected at length on challenges and triumphs they had embedding Indigenous knowledge and having students engage with it. Clinical partners from practice highlighted the need to ensure students had opportunities to engage with and learn from Indigenous people. Exploring the recommendations of clinical partners, who currently work with students attending placement in Indigenous communities provided valuable insights into what additional support students may require. Further work involved reaching consensus on the draft WRAP (Working Respectfully with Aboriginal People) Toolkit inclusions in consultation with Indigenous Elders.